2020
DOI: 10.1111/1753-6405.12957
|View full text |Cite
|
Sign up to set email alerts
|

How would the tobacco retail landscape change if tobacco was only sold through liquor stores, petrol stations or pharmacies?

Abstract: The authors have stated the following conflict of interest: Although we do not consider it a competing interest, for the sake of full transparency we note that authors have undertaken work for health sector agencies working in tobacco control. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Previous studies have evaluated a single or small number of policies [17][18][19]21,22], and few have evaluated the equity impact [21,22]. We explicitly evaluated density reduction and equity-impact of twelve potential policies selected based on previous research, many of which have been considered elsewhere [19,[21][22][23][24]. We used data on the real-world location of tobacco retailers to create continuous TOD surfaces as the basis for simulations, rather than hypothetical distributions at aggregate small area level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have evaluated a single or small number of policies [17][18][19]21,22], and few have evaluated the equity impact [21,22]. We explicitly evaluated density reduction and equity-impact of twelve potential policies selected based on previous research, many of which have been considered elsewhere [19,[21][22][23][24]. We used data on the real-world location of tobacco retailers to create continuous TOD surfaces as the basis for simulations, rather than hypothetical distributions at aggregate small area level.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have quantified the impact of such policies on overall TOD [17,18], or the cost of tobacco products [19,20]. Few studies have explicitly focused on the equity-impact of prospective policy interventions to control tobacco availability, but those that have showed that the equityimpacts of different policy options vary widely [21][22][23]. For example, the removal of tobacco sales from US pharmacies had no impact on existing racial/ethnic and socioeconomic disparities in TOD across neighbourhoods [21]; whereas banning tobacco sales within 1000 feet of schools may either reduce or eliminate existing disparities [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that tobacco outlet proximity is expected to be marginally affected by tobacco sales bans in supermarkets and petrol stations. Tobacco outlets will remain accessible within 500 m of postcode centroids, which would be a 5.5 min walk or 2.5 min bicycle ride 40. Tobacco outlet proximity is an important aspect of tobacco control, as it affects smoking outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We selected and report on the most relevant and illuminating documents, particularly those in which PMAI Research on placement of tobacco products in the retail spaces has been an accelerating area of tobacco control research (Abdel Magid et al, 2020;Anesetti-Rothermel et al, 2020;Glasser and Roberts, 2021;Lawman et al, 2020;Marsh et al, 2020;Marsh et al, 2021;Morrison et al, 2021;Pike et al, 2019;Pollay, 2007;Rodriguez et al, 2014;Shareck et al, 2020;Trapl et al, 2020;Valiente et al, 2020). Between 1999 and 2013, a few studies on tobacco retail placement were published in the international literature (Dewhirst, 2004;Feighery et al, 2003;Halonen et al, 2014;Lavack and Toth, 2006;Pollay, 2007;Rodriguez et al, 2014), then from 2016 increasing to more than a dozen (Abdel Magid et al, 2020;Anesetti-Rothermel et al, 2020;Glasser and Roberts, 2021;Lawman et al, 2020;Marsh et al, 2020;Marsh et al, 2021;Morrison et al, 2021;Pike et al, 2019;Shareck et al, 2020;Trapl et al, 2020;Valiente et al, 2020). Most studies on tobacco retail sales have been conducted in high-income countries, although a few studies have been conducted in Southeast Asia, including in Thailand (Li et al, 2015;Noosorn, 2019, 2020).…”
Section: Methodsmentioning
confidence: 99%